2019
DOI: 10.1039/c9ob01931f
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of N-1,2,4-oxadiazole substituted sulfoximines from N-cyano sulfoximines

Abstract: A divergent approach with a wide substrate scope has been successfully developed for the synthesis of N-1,2,4-oxadiazole tethered sulfoximines starting from N-cyano sulfoximines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Saravanan et al reported the facile synthesis of N-1,2,4-oxadiazole substituted sulfoximines from N-cyano sulfoximines (Scheme 14).This method involves the utilization ofa wide range of substrate thatincludes alkyl, fluoroalkyl, aryl, heteroaryl and saturated heterocyclic compounds. The major advantage of this method is metal-free and the utility of environmentally friendly solvents such as 2-methyl THF and ionic liquids [61]. Bharatiya et al reported the green and efficient microwave one-pot synthetic approachto N-phenyl piperazinyl-1,3,4-oxadiazole derivatives (Scheme 15) and evaluation of their antioxidant and antiinflammatory activity.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Saravanan et al reported the facile synthesis of N-1,2,4-oxadiazole substituted sulfoximines from N-cyano sulfoximines (Scheme 14).This method involves the utilization ofa wide range of substrate thatincludes alkyl, fluoroalkyl, aryl, heteroaryl and saturated heterocyclic compounds. The major advantage of this method is metal-free and the utility of environmentally friendly solvents such as 2-methyl THF and ionic liquids [61]. Bharatiya et al reported the green and efficient microwave one-pot synthetic approachto N-phenyl piperazinyl-1,3,4-oxadiazole derivatives (Scheme 15) and evaluation of their antioxidant and antiinflammatory activity.…”
Section: Miscellaneousmentioning
confidence: 99%
“…This method involves the utilization ofa wide range of substrate thatincludes alkyl, fluoroalkyl, aryl, heteroaryl and saturated heterocyclic compounds. The major advantage of this method is metal-free and the utility of environmentally friendly solvents such as 2-methyl THF and ionic liquids [61]. Staphylococcus aureus, which are pathogenic in human beings by cup plate agar diffusion method.…”
Section: Miscellaneousmentioning
confidence: 99%